The Influence of Celebrity Endorser and Brand Image on Purchase Decision of Vans Shoes (Case Study on Vans Shoe Consumers in Depok City) - Lestari, Hayu Putri Julia; Sudari, Suci Ayu; Pambreni, Yuni (Lead Journal of Economy and Administration, 2025)
This study aims to analyze the influence of celebrity endorsers and brand image on purchasing decisions of Vans shoes, with a case study on Vans shoe consumers in Depok City. The background of this research is based on the intense competition in the Indonesian footwear industry and the fluctuating sales of Vans products, highlighting the need for more effective marketing strategies. This research employs a quantitative approach using a survey method through questionnaires. The sample consists of Vans shoe consumers in Depok City. The results indicate that both the celebrity endorser and brand image variables have a significant partial effect on purchasing decisions. Furthermore, the variables also show a significant simultaneous effect on purchasing decisions. The independent variables collectively explain 41.6% of the variance in the dependent variable. These findings suggest that the presence of public figures can attract consumer attention, and a strong brand image plays a crucial role in influencing purchasing decisions. Therefore, it is recommended that companies place greater emphasis on marketing strategies, particularly concerning celebrity endorsers and brand image.